5‐1: Invited Paper: Booming Flexible Applications Enabled by AMOLED Technologies. Issue 1 (May 2017) - Lin, Yu-Hsin; Lee, Meng-Ting; Huang, Annie T.
Abstract : The flexible AMOLED technology allows us to create new applications because of its unique bendable and foldable properties. With the concept of placing the most fragile layers closed to the neutral plane of the devices, we are able to increase the reliability of flexible displays. Various applications will be introduced including a smart watch with fully circular design, a bendable display with novel interactive interface and a 7.8″ foldable display for phone‐tablet 2‐in‐1 application.